2021
DOI: 10.1364/ome.434475
|View full text |Cite
|
Sign up to set email alerts
|

Aligning silver nanowire films with cellulose nanocrystal nematics

Abstract: Anisotropic plasmonic films are a desirable material for many optoelectronic applications. Here, we propose a method to align silver nanowires (AgNWs) with the help of uniaxial nematic alignment of cellulose nanocrystal (CNC) liquid crystals (LCs) that can preserve their LC orientation in solid film. AgNWs are doped into uniaxial nematic CNC LCs, where AgNWs are oriented parallel to the director of shear- aligned CNCs without aggregation. The AgNWs orientations are determined by polarized optical and dark fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It has been previously reported that CNCs can aid in aligning high-aspect-ratio nanowires by preventing aggregation and enhancing orientational order. 34,35 In our case, CNCs facilitate the alignment of much smaller nanorods under shear. Our observation of uniaxial alignment of coassembled composite system is consistent with oriented, low-aspect-ratio gold nanorods mixed with CNCs as demonstrated by Liu et al 20 Although Liu's study was limited to low loading of gold nanorods, they did not calcine the material to remove organics.…”
Section: ■ Introductionmentioning
confidence: 63%
“…It has been previously reported that CNCs can aid in aligning high-aspect-ratio nanowires by preventing aggregation and enhancing orientational order. 34,35 In our case, CNCs facilitate the alignment of much smaller nanorods under shear. Our observation of uniaxial alignment of coassembled composite system is consistent with oriented, low-aspect-ratio gold nanorods mixed with CNCs as demonstrated by Liu et al 20 Although Liu's study was limited to low loading of gold nanorods, they did not calcine the material to remove organics.…”
Section: ■ Introductionmentioning
confidence: 63%